Contraceptive methods and knowledge of sexually transmitted diseases in nursing students. Results from a survey conducted at the University of Palermo (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The main purpose of the study was to evaluatesexual habits, sexual relations and knowledge of sexually transmitted infections (STIs) among the students in the nursing science course of University of Palermo, and to evaluate the use of contraceptive methods. Methods: In April 2019, a survey was provided to students who attend daily lessons in the nursing science course of University of Palermo, that investigate primarily about sexual habits, sexual relations and knowledge of sexually transmitted diseases. A multivariable logistic regression was performed. Results: The sample size consists of 405 students. The average age of the sample is 21.65 years, 69.63% of the interviewees are women. In relation to the question “Do you think you are sufficiently informed to be able to avoid risks of infection from sexually transmitted diseases? No”, the analysis shows that this independent variable is significantly associated with the following independent variables: female gender (aOR 3.11, 95% CI 1.01 - 9.65); “how would you define your knowledge about contraceptive methods? - Poor” (aOR 5.38, 95% CI 1.79 - 16.20); “have you ever received information on sex education and/or sexually transmitted diseases? - No” (aOR 11.59, 95% CI 2.26 - 59.42); “do you know the human papillomavirus (HPV) vaccination? - yes, but I’m not vaccinated” (aOR 3.09, 95% CI 1.12 - 8.51); “do you know that men can also undergo HPV vaccination? - No” (aOR 2.67, 95% CI 1.01 - 7.04). Conclusion: Based on our findings, it is necessary to implement sexual education programs for the improvement of knowledge in terms of STIs and the promotion of health. Improving sexual health outcomes for young people is a priority for the public health.